2019
DOI: 10.1016/j.cub.2019.09.067
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and Surprise Jointly Predict Musical Pleasure and Amygdala, Hippocampus, and Auditory Cortex Activity

Abstract: Highlights d Musical pleasure depends on prospective and retrospective states of expectation d A machine-learning model quantified the uncertainty and surprise of pop song chords d Chords with low uncertainty and high surprise, and vice versa, evoked high pleasure d Joint effects of uncertainty and surprise found in the amygdala and auditory cortex

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
191
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(206 citation statements)
references
References 78 publications
(141 reference statements)
11
191
1
3
Order By: Relevance
“…The PPM models used in prior cognitive research (Barascud et al, 2016;Cheung et al, 2019; Gold, Pearce, Mas-Herrero, Dagher, & Zatorre, 2019) have a 'perfect' memory, in that historic n-gram observations are preserved with the same fidelity as recent events, and are weighted the same in prediction generation. Noting that human memory exhibits clear capacity limitations and recency effects, Harrison et al (2020) modified PPM to incorporate a customizable decay kernel, whereby historic n-gram observations are down-weighted as a function of the time elapsed and the consequent n-grams observed since the initial observation.…”
Section: Ppm-decay Modelmentioning
confidence: 99%
“…The PPM models used in prior cognitive research (Barascud et al, 2016;Cheung et al, 2019; Gold, Pearce, Mas-Herrero, Dagher, & Zatorre, 2019) have a 'perfect' memory, in that historic n-gram observations are preserved with the same fidelity as recent events, and are weighted the same in prediction generation. Noting that human memory exhibits clear capacity limitations and recency effects, Harrison et al (2020) modified PPM to incorporate a customizable decay kernel, whereby historic n-gram observations are down-weighted as a function of the time elapsed and the consequent n-grams observed since the initial observation.…”
Section: Ppm-decay Modelmentioning
confidence: 99%
“…Notably, bodily reactions such as 'chills' which are generally associated with particularly intense and pleasurable responses to music, and have been associated with greater engagement of the NAcc (Grewe et al, 2009(Grewe et al, , 2005Mas-Herrero et al, 2018b;Salimpoor et al, 2009), are often experienced following musical surprises (Grewe et al, 2007;Guhn et al, 2007;Harrison and Loui, 2014;Nagel et al, 2008;Panksepp, 1995;Sloboda, 1992). Finally, recent studies using an information-theoretic model of auditory expectation indicate that listeners may prefer music containing surprises, yet in a context in which those can be learned and anticipated (Cheung et al, 2019;Gold et al, 2019b). These findings resonate with learning theories that suggest that the information gain of balancing uncertainty and surprise (Oudeyer et al, 2016) could be intrinsically rewarded by the brain in order to foster our fundamental need of generating accurate models of the world.…”
Section: The Striatummentioning
confidence: 99%
“…For instance, while hedonic reactions and preference for primary tastes, such as sweetness, are largely innate and highly preserved across species and individuals (Berridge, 2000), musical preferences are shaped by previous exposure, cognitive abilities, musical education, and cultural background; thus they are largely influenced by learning and plasticity (Gold et al, 2019b(Gold et al, , 2019aGreenberg et al, 2015;Haumann et al, 2018). In this regard, recent models hold that music-induced pleasure may be driven by anticipation and prediction mechanisms, which, in turn, have been linked to predictive coding theories (Cheung et al, 2019;Gold et al, 2019b;Koelsch et al, 2019;Salimpoor et al, 2015). In line with this idea, neuroimaging studies have shown that music-induced pleasure may be mediated by the crosstalk between the ancient reward circuitry and higher-order cortical regions involved in auditory cognition and predictive coding that are phylogenetically newer and especially well developed in humans, such as the superior temporal gyrus and the inferior frontal gyrus (Loui et al, 2017;Martínez-Molina et al, 2016;Sachs et al, 2016;Salimpoor et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Abstract rewards such as music are strongly dependent upon perceptual expectations and predictions (Meyer, 1956). In the context of prediction, data posits that dopaminergic neurons in the VS (and Nucleus Accumbens) are the key factor driving the attachment of hedonic value to music (Salimpoor et al, 2015;Gold et al, 2019; but see Cheung et al, 2019). Reward prediction errors (RPEs) are also crucial for reinforcement learning processes (Sutton and Barto, 2018), and growing evidence suggests that they play a pivotal role in episodic memory (Davidow et al, 2016;De Loof et al, 2018;Calderon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Music-induced pleasure relies on the activity of core reward regions within the mesolimbic dopaminergic system (Blood and Zatorre, 2001;Salimpoor et al, 2011Salimpoor et al, , 2013Koelsch, 2014;Mas-Herrero et al, 2018;Ferreri et al, 2019). Both theoretical considerations and recent experimental findings suggest that music represents a learning challenge by itself-triggered by the presence and violation of musical regularities-and that reward-related activations induced by music may be driven by the intrinsic value of successfully anticipating potential musical surprises (Koelsch et a., 2019;Gold et al, 2019;Cheung et al, 2019). Interestingly, humans show significant individual differences in sensitivity to musical pleasure, and this variance is related to brain structure and function in the reward circuitry, and its interactions with the auditory perceptual system (Mas-Herrero et al, 2013Martinez-Molina et al, 2016).…”
Section: Introductionmentioning
confidence: 99%